2018
DOI: 10.2147/cmar.s168579
|View full text |Cite
|
Sign up to set email alerts
|

The homogeneous and heterogeneous risk factors for the morbidity and prognosis of bone metastasis in patients with prostate cancer

Abstract: Purpose Using the Surveillance, Epidemiology, and End Results database (SEER) to assess the incidence and risk factors of morbidity and prognosis for bone metastases in initial metastatic prostate cancer. Patients and methods The records of 249,331 prostate cancer patients in the SEER database, diagnosed between 2010 and 2014, were obtained were obtained to investigate the risk factors for developing bone metastasis, and the records of 9925 of them who registered before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 17 publications
6
29
0
Order By: Relevance
“…However, no information on the detailed surgical approaches adopted among osteosarcoma patients was recorded in the public SEER database. 19 to the limited sample size, we could not maintain enough statistical power to get a more stable result and, consequently, further studies are needed in order to confirm these results.…”
Section: Discussionmentioning
confidence: 92%
“…However, no information on the detailed surgical approaches adopted among osteosarcoma patients was recorded in the public SEER database. 19 to the limited sample size, we could not maintain enough statistical power to get a more stable result and, consequently, further studies are needed in order to confirm these results.…”
Section: Discussionmentioning
confidence: 92%
“…Patients with cancer of the uterine cervix have been reported to have a relatively lower incidence of bone metastases when compared with cancer of the breast, lung, and prostate [ 17 19 ]. The present study showed that 2.42% of the study cohort of women with cervical cancer had bone metastases when initially diagnosed, which was a similar finding to that of the study conducted by Thanapprapasr et al (1.1%) [ 6 ], but was lower than that found in other studies [ 8 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic factors in the cancer patients with distant metastases have been widely studied [14][15][16].…”
Section: Ivyspringmentioning
confidence: 99%